The Feasibility, Safety, and Efficacy of Using a Wireless Pedometer to Improve the Activity Level in a Cohort of Nurses. (June 2017) - Flanagan, Jane; McCord, Ann; Cheney, Michael; Lundquist, Debra
Purpose: This study had two aims: (1) to test the feasibility, safety, and efficacy of using a wireless pedometer in a cohort of nurses; and (2) to understand if wireless pedometer use increased number of steps walked, number of flights of stairs climbed, daily activity level, and improved personal perception of health.Design: This study used a nonexperimental exploratory design to test the feasibility and efficacy of using a wireless pedometer in a cohort of nurses. Pre- and posttest measures captured the number of steps walked, flights of stairs climbed, activity level, and perception of health.Results: Sample characteristics: 27 females, 3 males; 90% non-Hispanic Caucasian, 3% Hispanic; 47% between the ages of 55 and 65 years. Eighty percent of the participants reported that they were caregivers of other people. There was a significant increase from baseline to the end of the study in the following measures: self-perception of steps walked ( p < .001), flights of stairs climbed ( p < .005), self-perception of daily activity ( p < .001), and although there was an improvement in self-perception of health, the change was not significant.Conclusions: The wireless pedometer was a feasible, safe, and efficacious device to use. This study may have implications for interventions aimed at improving caregiver health.